ANALISIS PROFITABILITAS BERDASARKAN SALURAN DISTRIBUSI PENJUALAN PRODUK HOME INDUSTRI KERUPUK LANTING DI KECAMATAN PASIR PENYU - Indah Kesuma Noer; Gimin Gimin; Gani Haryana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the level of profitability of the lanting cracker home industry in Pasir Penyu District. The population in this study was the home industry of lanting crackers in Pasir Penyu Subdistrict totaling 8 home industries, and which were sampled as many as 8 lanting cracker home industries, with the sampling technique using total sampling. Measurement of data using interviews. Analysis of the data used is descriptive analysis. The results of the descriptive research show that from the calculation of profitability in the home of the lanting cracker industry in Pasir Penyu Subdistrict, the cost of production costs around Rp. 800,000 - Rp. 1,800,000 per month. The profit earned by the home of the lanting cracker industry can reach IDR 900,000 - IDR 2,500,000 per month depending on the cost of production, product prices, and the number of products. Profitability in the lanting cracker home industry that uses direct distribution channels has a profit of IDR3,517 while the lanting cracker home industry that uses an indirect distribution channel is only IDR2,468.Key Words: Profitability, Industrial Home Products